A Proposed Grading Scheme for Medullary Thyroid Carcinoma Based on Proliferative Activity (Ki-67 and Mitotic Count) and Coagulative Necrosis. (October 2020) - Fuchs, Talia L.; Nassour, Anthony J.; Glover, Anthony; Sywak, Mark S.; Sidhu, Stan B.; Delbridge, Leigh W.; Clifton-Bligh, Roderick J.; Gild, Matti L.; Tsang, Venessa; Robinson, Bruce G.; Clarkson, Adele; Sheen, Amy; et al.
Abstract : We investigated the prognostic value of a range of histologic parameters in medullary thyroid carcinoma (MTC) to design a grading system to predict overall survival. We assessed 76 patients with MTCs undergoing primary tumor resection for age, sex, tumor size, vascular space invasion, lymph node metastasis, multiple endocrine neoplasia type 2 (MEN2) status, mitotic count, Ki-67 proliferative index, spindled morphology, sheet-like growth pattern, coagulative necrosis, incipient necrosis, nuclear grade, multinucleation, prominent nucleoli, fibrosis, and amyloid deposition. In addition to the clinical features of age and the diagnosis of MEN2, the only histologic features that significantly predicted reduced overall survival were Ki-67 proliferative index, mitotic count, and the presence of coagulative necrosis. Using a combination of these 3 variables, we propose a 3-tiered grading system based solely on proliferative activity (Ki-67 proliferative index and mitotic count) and necrosis. There were 62 (82%) low-grade MTCs (low proliferative activity, no necrosis), 9 (12%) intermediate grade (low proliferative activity and necrosis present, or intermediate proliferative activity and no necrosis), and 5 (7%) high grade (intermediate proliferative activity and necrosis present, or high proliferative activity with or without necrosis). The mean overall survival was 193, 146, and 45 months, respectively ( P =0.0001) for the 3 grades. The grading system remained prognostic when controlled for other factors associated with survival including age and known MEN2 syndrome. We conclude that this proposed grading system, which uses only a combination of proliferative activity (Ki-67 index, mitotic count) and coagulative necrosis, is a strong predictor of overall survival in MTC.